Subtitling and the promotion of multilingualism: the case of marginalised languages in South Africa - Kruger, Jan-Louis; Kruger, Haidee; Verhoef, Marlene (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article investigates the role that subtitling may play in the promotion of multilingualism in South Africa. After a reflection on the current language-political situation in the country, in particular as it pertains to the public broadcaster, the findings of a pilot study focusing on the role of subtitling in promoting multilingualism and language rights in South Africa are presented. The research involves aspects such as language status, attitudes and acquisition, focusing on two of the more marginalised languages in the country, namely Tshivenda and Xitsonga. It also touches on the impact of subtitling on comprehension.